Adverse effects to food supplements containing botanical ingredients. (September 2020) - Colombo, Francesca; Di Lorenzo, Chiara; Biella, Simone; Vecchio, Sarah; Frigerio, Gianfranco; Restani, Patrizia
Graphical abstract: Highlights: The high diffusion of Plant Food Supplements raised concerns about their safety. Adverse effects due to PFS are normally mild but some fatal case occurred. Green tea and valerian were the plants most frequently involved in adverse effects. Prebiotic fibers were often involved in adverse effects on gastrointestinal system. Abstract: The use of Plant Food Supplements (PFS) has increased significantly in the last decades. The wide diffusion of these products has raised concerns about their safety and to solve at least some critical points the EU Project PlantLIBRA was financed. The project included among its goals the collection of adverse effects due to PFS; using different sources: 1) the scientific literature; 2) European Poison Centers; 3) the PlantLIBRA consumer survey. New data from the Pavia Poison Centre, ANSES and FDA were elaborated after the end of EU Project. Adverse effects were analysed according to the WHO causal relationship criteria. Valeriana officinalis and Camellia sinensis were the plants most frequently involved in adverse effects in European countries. Although mild/moderate symptomatology were generally described, some severe outcomes occurred, including fatal cases. Nervous and gastrointestinal systems were the main targets; the intestinal disorders were associated with fibres and polyphenols present in some plants.